Computer Attitudes and Use Among Novice Teachers: The Moderating Effects of School Environment (Malaysian Journal of Learning and Instruction, 2010)
Purpose âˆ’ This survey research investigated important issues concerning computer use among novice graduate teachers from teacher training colleges in Sabah. The first issue was concerned with the levels of computer attitudes (CA) and computer use. The second was concerned with the effects of CA on computer use (CU). The third was concerned with moderating effects of the school environment (SE) on relationship between CA and computer use. Method âˆ’ A set of questionnaires was used as the research instrument and stratified systematic sampling was used to determine the research samples. The sample consisted of 192 primary and secondary school teachers. The data were analyzed using descriptive and inferential statistics (factor analysis and regression analysis). Research hypotheses were tested at significance level of a = 0.05. Findings âˆ’ The findings showed that novice teachers have moderate CA and CU. CA had significant effects on computer use. SE has moderating impacts on the relationships between CA towards CU. Value âˆ’ The study provided wider implications for theory development, practices and policymaking that can be associated with the computer use among teachers. As a whole, most of the theoretical rationales used in explaining those relationships have been supported.